Impact of endemic Besnoitiosis on the performance of a dairy cattle herd - Anastácio, Catarina (2022)
This study aimed to assess the effect of Besnoitia besnoiti infection on the reproductive and productive performance of a dairy cattle herd. A serological screening was performed by indirect fluorescent antibody test (IFAT) on every animal aged over one year (n = 262). Subsequently, 211 animals were clinically examined, with 96 of those being screened for detection of sclerocysts. The overall seroprevalence was 62.9% (CI95%: 56.1–69.5%). On clinical examination, 7.6% (16/211) of the animals presented chronic skin lesions, and 47.9% (46/96) had sclerocysts. Multivariate logistic regression showed that the time on the herd represented a risk factor. The odds of acquiring the infection increased 1.683× per additional year on the herd, ranging from less than a year to 8 years. Seropositivity and the presence of sclerocysts revealed an association with a higher milk somatic cell count, which may have a considerable economic impact on dairy production. Regarding reproductive indicators, no negative effect could be associated with clinical besnoitiosis or positive serological results. In conclusion, our study highlights the need to thoroughly evaluate the economic impact of this emerging disease in dairy herd production to help with decision-making at both herd and regional levels, particularly in endemic areas.